Content and Delivery of Physical Therapy in Multiple Sclerosis across Europe: A Survey - Řasová, Kamila; Freeman, Jenny; Cattaneo, Davide; Jonsdottir, Johanna; Baert, Ilse; Smedal, Tori; Romberg, Anders; Feys, Peter; Alves-Guerreiro, Jose; Habek, Mario; Henze, Thomas; Santoyo-Medina, Carme; et al. (International journal of environmental research and public health, 2020)
Background: Guidelines and general recommendations are available for multiple sclerosis rehabilitation, but no specific guidance exists for physical therapists. Describing aspects of physical therapy content and delivery in multiple sclerosis and its determinants and analysing whether general recommendations connected with physical therapy are implemented in practice is important for interpreting clinical and research evidence. Methods: An online cross-sectional survey of physical therapists specialized in multiple sclerosis (212 specialists from 26 European countries) was used. Results: There was distinct diversity in service delivery and content across Europe. Perceived accessibility of physical therapy varied from most accessible in the Western region, and least in the Southern region. Sixty-four physical therapists adjusted their approach according to different disability levels, less so in the Eastern region. Duration, frequency and dose of sessions differed between regions, being highest in Southern and Western regions. "Hands on treatment" was the most commonly used therapeutic approach in all apart from the Northern regions, where "word instruction" (providing advice and information) prevailed. Conclusions: The content and delivery of physical therapy differs across Europe. Recommendations concerning access to treatment and adjustment according to disability do not appear to be widely implemented in clinical practice.
Keywords: Surveys and Questionnaires; questionnaire survey; Humans; professional guidelines; lidé středního věku; Multiple Sclerosis; Female; mladý dospělý; dospělí; lidé; Europe; průzkumy a dotazníky; Physical Therapy Modalities; Adult; ženské pohlaví; multiple sclerosis; roztroušená skleróza; Male; Middle Aged; Delivery of Health Care; poskytování zdravotní péče; Cross-Sectional Studies; Young Adult; techniky fyzikální terapie; mužské pohlaví; physical therapy; průřezové studie; Evropa